2014
DOI: 10.1128/jb.01527-14
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation Interplay between Variants of the RepA-WH1 Prionoid in Escherichia coli

Abstract: The N-terminal domain (winged-helix domain, or WH1) of the Pseudomonas pPS10 plasmid DNA replication protein RepA can assemble into amyloid fibers in vitro and, when expressed in Escherichia coli, leads to a unique intracellular amyloid proteinopathy by hampering bacterial proliferation. RepA-WH1 amyloidosis propagates along generations through the transmission of aggregated particles across the progeny, but it is unable to propagate horizontally as an infectious agent and is thus the first synthetic bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

6
2

Authors

Journals

citations
Cited by 16 publications
(55 citation statements)
references
References 31 publications
(46 reference statements)
1
54
0
Order By: Relevance
“…A construct just carrying the mCherry protein (Molina-García and Giraldo, 2014) was used as a control. As bacterial host, the reduced genome E. coli K-12 strain MDS42 recA (Pósfai et al, 2006) was used in all experiments because it provides a simplified ‘chassis’ carrying the essential metabolic and regulatory pathways.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A construct just carrying the mCherry protein (Molina-García and Giraldo, 2014) was used as a control. As bacterial host, the reduced genome E. coli K-12 strain MDS42 recA (Pósfai et al, 2006) was used in all experiments because it provides a simplified ‘chassis’ carrying the essential metabolic and regulatory pathways.…”
Section: Methodsmentioning
confidence: 99%
“…RepA-WH1 fibers are of amyloid nature, as indicated by Congo red binding (Giraldo, 2007), and by a net increase in the protein β-sheet contents, according to both circular dichroism (Giraldo, 2007; Torreira et al, 2015) and surface-enhanced Raman (Fernández et al, 2016a) spectroscopies. In our efforts to engineer a synthetic bacterial amyloid proteinopathy, we found that the amyloidogenicity of WH1(A31V) in E. coli cells can be boosted displacing its conformational equilibrium toward partial unfolding by fusing a protein to its C-terminus, distinct to the natural WH2 domain in RepA (Giraldo et al, 2003): the monomeric fluorescent protein mCherry (Fernández-Tresguerres et al, 2010; Gasset-Rosa et al, 2014; Molina-García and Giraldo, 2014). In the resulting fusion protein, for simplification hereafter WH1(A31V)-mCh (biophysically characterized in Fernández et al, 2016b), the mCherry tag has not a direct contribution to aggregation, because a fusion of mCherry to wild-type RepA-WH1 remained soluble and non-toxic in the cytoplasm (Fernández-Tresguerres et al, 2010; Molina-García and Giraldo, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…from mother to daughter cells) as two distinct aggregate strains with remarkable appearances and phenotypes: elongated and mildly cytotoxic, and compact and acutely cytotoxic, respectively (Gasset-Rosa et al, 2014). Co-expression of soluble and aggregation-prone RepA-WH1 variants in E. coli demonstrated that the A31V variant can template its conformation on the parental WT protein (Molina-García and Giraldo, 2014). Systems analyses (Molina-García et al, 2017), together with in vitro reconstruction in cytomimetic lipid vesicles (Fernández et al, 2016b; Fernández and Giraldo, 2018), suggest that RepA-WH1(A31V) oligomers target the internal bacterial membrane, hampering proton motive force and thus ATP synthesis and transport through membranes, and enhance oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…29 This protein, when modified, generated a prion-like disease in bacteria that can be transmitted from mother to daughter cells. 30 More recently, this group showed that this bacterial prionoid can seed amyloid aggregation of mutants from the same protein, 31 and characterized the bacterial nucleoid as the initial site of assemble of these prionlike aggregates. 32 This bacterial amyloidosis, shared some characteristics with mammalian prion diseases, mainly transmissibility and the presence of phenotypically distinct strains.…”
Section: Introductionmentioning
confidence: 99%